The role of human leucocyte antigen in nasopharyngeal carcinoma - Rahman, Sukri; Sari, Jenny Tri Yuspita; Grecwin, Debby Apri; Hafiz, Al (Oto Rhino Laryngologica Indonesiana, 2022)
ABSTRACTBackground: The cause of Nasopharungeal Carcinoma (NPC) is an interaction of multiple factors. The main etiologic factors are Epstein-Barr virus (EBV) infection which interacts with genetic susceptibility, and environmental factors. The growth of malignancy due to the virus is largely determined by the host immune response. Human leukocyte antigen (HLA) plays a significant role in presenting viral antigens, which is the key in determining the impact of the host immune response against this viral infection. Purpose: To discuss the role of HLA in NPC. Literature review: Individuals with specific HLA alleles may experience a decreased ability to present viral antigens and be less efficient in triggering an immune response against EBV-infected cells resulting in increased susceptibility to NPC and vice versa, so those specific HLA alleles may be protective. Various studies have reported the association of HLA alleles with NPC. The results of these studies are not always consistent. In the study of HLA class I, HLA-A2 and HLA-B46 alleles were the most consistently increasing frequency in NPC, while HLA-A11, HLA-B13, and HLA-B27 alleles were associated with a decreased risk of NPC. The HLA-DRB1*03, *08, *09, and *10 alleles contributed to susceptibility to NPC, while the HLA-DRB1*11 and *12 alleles were protective factors against NPC. Conclusion: Genetic factors are important risk factors for NPC, many studies have consistently reported the role of HLA in the pathogenesis of NPC, where specific HLA alleles cause susceptibility to NPC growth, but several HLA alleles are also associated with a reduced risk of NPC.ABSTRAKLatar belakang: Penyebab terjadinya Karsinoma Nasofaring (KNF) merupakan interaksi dari beberapa faktor. Faktor etiologi utama adalah infeksi virus Epstein-Barr (EBV) yang berinteraksi dengan kerentanan genetik, dan faktor lingkungan. Pertumbuhan keganasan akibat virus sangat ditentukan oleh respon imun host. Human Leucocyte Antigen (HLA) berperan penting dalam penyajian antigen virus, yang merupakan kunci dalam menentukan dampak respon imun host terhadap infeksi virus ini. Tujuan: Membahas peran HLA pada KNF. Tinjauan pustaka: Individu dengan alel HLA spesifik dapat mengalami penurunan kemampuan untuk mempresentasikan antigen virus dan kurang efisien dalam memicu respon imun terhadap sel yang terinfeksi EBV yang mengakibatkan peningkatan kerentanan terhadap KNF dan sebaliknya, sehingga alel HLA tertentu mungkin bersifat protektif. Berbagai penelitian telah melaporkan hubungan alel HLA dengan KNF. Hasil dari berbagai penelitian tersebut tidak selalu konsisten. Pada studi HLA kelas I, alel HLA-A2 dan HLA-B46 adalah yang paling konsisten frekuensinya meningkat pada KNF, sedangkan alel HLA-A11, HLA-B13 dan HLA-B27 dikaitkan dengan penurunan risiko KNF. Alel HLA-DRB1*03, *08, *09 dan *10 berkontribusi terhadap kerentanan terhadap KNF, sedangkan alel HLA-DRB1*11 dan *12 merupakan faktor protektif terhadap KNF. Kesimpulan: Faktor genetik merupakan faktor risiko penting pada KNF, berbagai penelitian konsisten melaporkan peran HLA dalam patogenesis KNF, di mana alel HLA tertentu menyebabkan kerentanan terhadap pertumbuhan KNF, sementara beberapa alel HLA juga terkait dengan penurunan risiko KNF.